Influence of sowing season on some quality indices for soybean - Popa, Alin; Simon, Alina; Ceclan, Adrian; Rezi, Raluca; Urda, Camelia; Bardas, Marius; Chetan, Felicia (International Journal of Sustainable Agricultural Research, 2023)
Soybean quality indices, like yield, can be influenced by factors such as climatic conditions, applied technology or biological material. Soybean is a short-day species with moderate temperature requirements, especially during flowering, a critical period for achieving yield and crop quality, air temperature in the range of 17-18°C is considered the biological minimum, while the range of 22-25°C is considered optimal. High temperatures during the flowering period can cause significant yield losses through flower abortion especially when correlated with insufficient humidity. This paper presents summary data obtained in soybean cultivation under the conditions of the Transylvanian Plateau at Agricultural Research and Development Turda on the influence of sowing time on some quality indices. The experiment was realized using the block method in subdivided plots with 3 factors AxBxC on a type soil chernozem, characteristic of the Transylvanian Plateau with chemical description, the soil has a neutral to low alkaline pH, neutral to high humus content, well supplied in nitrogen and potassium, medium supplied in phosphorus. During three experimental years 2021 - 2023 climatic conditions and sowing times influenced differently the protein and fat content of 5 soybean varieties. The results obtained were statistically processed by the analysis of variance method and determination of the least significant difference - LSD - (5%, 1% and 0.1%).